Eskatologi Dalam Teks Geguritan Atma Prasangsa (Kajian Teks dan Konteks) - Anak Agung Raka Asmariani; I Nyoman Suarka; I Nengah Duija (Jayapangus Press, 2019)
Hindu talks much about heaven and hell differently from other religion’s explanation. Heaven and hell are closely related and integrated with Karma. Stories in some puranas discuss much about this escatology. On of the text in Indonesia talking much about this is Geguritan Atma prasangsa. This work descriptively describes in detail about heaven and hell, how a man can come to into heaven or hell, what happenes with the soul coming into hell, what kind of penalty applied, and also the principals. This texs tells in good sequences type of death including those wich cause the soul unable to find its way home. The texs also tells about how the soul screamed for being tortured the by the hell authority. And also the kind of perceived by the soul in heaven. How long a soul should be punished in hell or enjoy the heaven before finally reincarnated back to the word. After all joys and miseries experienced by the soul in accordance with their conducts during life finished, the soul sould be reincarnated to continue the journey.